Reduction in Cogging Torque and Flux per Pole in BLDC Motor by Adapting U-Clamped Magnetic Poles - M. Arun Noyal Doss; S. Vijayakumar; A. Jamal Mohideen; K. Sathiah Kannan; N.D. Balaji Sairam; K. Karthik (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
A Permanent Magnet BLDC motor is designed for reduction in cogging torque and flux per pole. The cogging torque causes direct impact in permanent magnet BLDC motor performance by causing torque ripple problems. This paper proposes a new method for reducing cogging torque by adapting to U-clamped magnetic poles. Finite Element Analysis (FEA) is used to calculate the cogging torque and the flux per pole for different shapes of magnetic pole. It can be shown that the cogging torque could be greatly reduced by adapting to U-clamped magnetic poles. At the same time it is found that the flux per pole is also considerably reduced. The effectiveness of the proposed method is verified by comparing the cogging torque and flux per pole for various designs available in the literature.